Sistem Pendukung Keputusan Pemilihan Persediaan Bahan Produksi dengan menggunakan Metode Weighted Product berbasis Android (Studi Kasus: Burger Moe) - Johan Fajar Eka; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Decision making in the supply chain process must be appropriate so that the production flow process that is run can run well. One form of decision making from a company is through a Decision Support System (DSS). The implementation of SPK on Burger Moe's supply chain process aims to help companies determine decisions on selecting raw materials for production more quickly according to existing needs and conditions in order to help the company run well. In determining the production of raw materials, the company determines several criteria as a reference, including purchase price, purchase distance, number of uses (weekly period), and durability. These criteria become the main guidelines in the DSS using the WP (Weighted Product) method. The WP method is used to rank the best raw materials from all available alternatives. To see the suitability between the DSS and the decision recommendations made manually by the user, this study used the Spearman correlation test which resulted in a value of 0.586. This value indicates that the decision support system and user decisions have a moderate relationship strength.